(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the possible side effects of cyclopentolate. Study Design: Observational study. Place and Duration of Study: This study was conducted at the Department of Ophthalmology, Mardan Medical Complex Mardan from May 2017- July 2017. Materials and Methods: 96 patients of age group from 1-8 years were examined with instillation of one drop of 1% cyclopentolate three times at the interval of 10-15 minutes. The possible side effects were then observed. Results: Most of the children were observed with more than one side effect like Blurred vision, Watering, Fever, Swelling of eye lids and Allergy etc to the drug. Bilateral swelling and laziness were also observed in few patients, not reported in previous literatures. Conclusion: Patients compliance was very poor due to side effects of these cycloplegic drug. So to improve the patient compliance, so to minimize the side effects of cycloplegic drugs we need to use drugs with fewer side effects.